The sympathetic state : disaster relief and the origins of the American welfare state - Dauber, Michele Landis (Chicago : The University of Chicago Press, 2013)
Even as unemployment rates soared during the Great Depression, FDR's relief and social security programmes faced attacks in Congress and the courts on the legitimacy of federal aid to the growing population of poor. In response, New Dealers pointed to a long tradition - dating back to 1790 and now largely forgotten - of federal aid to victims of disaster. In 'The Sympathetic State', Michele Landis Dauber recovers this crucial aspect of American history, tracing the roots of the modern American welfare state beyond the New Deal and the Progressive Era back to the earliest days of the republic when relief was forthcoming for the victims of wars, fires, floods, hurricanes, and earthquakes.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Economic assistance, Domestic -- Law and legislation -- United States; Welfare state -- United States -- History; Disaster relief -- Government policy -- United States; Society; United States of America, USA; History; History of the Americas; History; Social services & welfare, criminology